Angiogenic imbalance in pregnancies with preterm prelabor rupture of membranes between 34 and 37 weeks of gestation - Kacerovsky, Marian; Hornychova, Helena; Jaiman, Sunil; Pavlikova, Ladislava; Holeckova, Magdalena; Jacobsson, Bo; Tsiartas, Panagiotis; Musilova, Ivana (Acta obstetricia et gynecologica Scandinavica, 2024)
INTRODUCTION: This study aimed to identify whether microbial invasion of the amniotic cavity and/or intra-amniotic inflammation in women with late preterm prelabor rupture of membranes (PPROM) was associated with changes in concentrations of soluble fms-like tyrosine kinase-1 (sFlt-1), placental growth factor (PlGF) and its ratio in maternal serum, and whether placental features consistent with maternal vascular malperfusion further affect their concentrations. MATERIAL AND METHODS: This historical study included 154 women with singleton pregnancies complicated by PPROM between gestational ages 34+0 and 36+6 weeks. Transabdominal amniocentesis was performed as part of standard clinical management to evaluate the intra-amniotic environment. Women were categorized into two subgroups based on the presence of microorganisms and/or their nucleic acids in amniotic fluid (determined by culturing and molecular biology method) and intra-amniotic inflammation (by amniotic fluid interleukin-6 concentration evaluation): (1) those with the presence of microorganisms and/or inflammation (at least one present) and (2) those with negative amniotic fluid for infection/inflammation (absence of both). Concentrations of sFlt-1 and PlGF were assessed using the Elecsys® sFlt-1 and Elecsys® PlGF immunoassays and converted into multiples of medians. RESULTS: Women with the presence of microorganisms and/or inflammation in amniotic fluid had lower serum concentrations of sFlt-1 and sFlt-1/PlGF ratios and higher concentrations of PlGF compared with those with negative amniotic fluid. (sFlt-1: presence: median 1.0 multiples of the median (MoM), vs negative: median: 1.5 MoM, P = 0.003; PlGF: presence: median 0.7 MoM, vs negative: median 0.4 MoM, P = 0.02; sFlt-1/PlGF: presence: median 8.9 vs negative 25.0, P = 0.001). Higher serum concentrations of sFlt-1 and sFlt-1/PlGF ratios as well as lower concentrations of PlGF were found in the subsets of women with maternal vascular malperfusion than in those without maternal vascular malperfusion. CONCLUSIONS: Among women experiencing late PPROM, angiogenic imbalance in maternal serum is primarily observed in those without both microbial invasion of the amniotic cavity and intra-amniotic inflammation. Additionally, there is an association between angiogenic imbalance and the presence of maternal vascular malperfusion.
Keywords: gestační stáří; dospělí; chorioamnionitida; Chorioamnionitis; Female; předčasný odtok plodové vody; biologické markery; Gestational Age; Amniocentesis; Biomarkers; Adult; ženské pohlaví; Placenta Growth Factor; lidé; těhotenství; placentární růstový faktor; receptor 1 pro vaskulární endoteliální růstový faktor; Fetal Membranes, Premature Rupture; Vascular Endothelial Growth Factor Receptor-1; amniocentéza; Amniotic Fluid; plodová voda; Pregnancy; Humans